The role of bracket fungi in creating alpha diversity of invertebrates in the Białowieża National Park, Poland - Anna K. Gdula (Ecology and Evolution, 2021)
Abstract Bracket fungi are seen mainly as the cause of economic losses in forestry, and their role as creators of biodiversity is relatively poorly understood. The aim of the study was defining the manner in which the degree of decay (DD) of the fruiting bodies determines the character of the invertebrate assemblages colonising them. The effect of this group of fungi on the modification of biodiversity of invertebrates (Aranae, Opiliones, Pseudoscorpionida, two groups of mites—Mesostigmata and Oribatida, and Collembola and Insecta) was investigated by analyzing 100 fruiting bodies of 10 species of bracket fungi divided into four DD classes. The material was collected at Białowieża National Park, which is considered to be the largest area of natural forests in the North European Plain. 16 068 invertebrate individuals classified into 224 species were obtained. Oribatid mites (12 543 individuals) constituted the largest group of individuals, which were classified into 115 species with the most numerous Carabodes femoralis (8,811 individuals). Representatives of this group of mites have been reported previously in the publications on bracket fungi; however, the contributions of Oribatida and other groups of invertebrates were not broadly compared. Moreover, the species such as Hoploseius mariae and H. oblongus, which were predominantly found in fruiting bodies of bracket fungi, have also been discerned. The invertebrate fauna differs depending on DD of the samples: In the more decayed samples, a higher number of both individuals and species were recorded compared to the samples with lower DDs; however, this trend proved to be nonlinear. The DCA and cluster analysis revealed a similarity of the invertebrate assemblages from the 2 DD and 4 DD samples. They also indicated that the group 3 DD differed the most from all the other samples. The indicator species analysis identified species characteristic to individual DDs: For group 1 DD, it was, for example, Hoploseius oblongus; for 2 DD—Orchesella bifasciata; and for 3 DD—Chernes cimicoides, while for 4 DD—Dinychus perforatus.